Contrast-enhanced ultrasound of collecting duct carcinoma in the renal: a case report misdiagnosed as renal abscess on computed tomography scan - Luo, Yunhao; Zhang, Jing; Wu, Minggang; Huang, Qiuyun; Liu, Fangqin; Qiao, Lang (Frontiers in Oncology, 2025)
Collecting duct carcinoma (CDC), also known as Bellini duct carcinoma, is a rare malignancy with significant challenges in early diagnosis. This paper presents a case report of CDC that was misdiagnosed as renal abscess on computed tomography (CT). A 49-year-old male patient was admitted to the hospital with bilateral lumbar pain, exacerbated on the left side, accompanied by hematuria. Following laboratory tests, CT scan, ultrasound, and contrast-enhanced ultrasound (CEUS), the CT diagnosis was renal abscess, whereas CEUS suggested a malignant tumor. After a multidisciplinary discussion, the patient underwent surgery and was diagnosed with CDC. Previous studies indicate that two-dimensional ultrasound of CDC often lack typical features, while CT and magnetic resonance imaging (MRI) scan usually show mild enhancement. CEUS has a unique advantage in visualizing the microvasculature, which aids in the diagnosis of CDC.